Determination of Valproic Acid without Derivatization in Human Plasma using High Performance Liquid Chromatography-Photodiode Array - Yahdiana Harahap (Journal of Global Pharma Technology, 2017)
Objective: To develop and validate a simple and sensitive HPLC method without derivatization for determination of valproic acid in human plasma. Methods: Nonanoic acid as internal standard was added to 500 mL of plasma sample prior to liquid-liquid extraction using n-hexane and 0.5% triethylamine. Chromatographic separation was achieved on C-8 Symmetry® column (5µm; 150 x 3.9mm) in isocratic mode at 45°C. The mobile phase was 40 mM sodium dihydrogen phosphate pH 3.5 – acetonitrile (56:44 %v/v) with flow rate of 1.00 mL/min and was detected at 210 nm. Method validation referred to EMA Guideline 2011 for bioanalytical method validation in term of parameters lower limit of quantification (LLOQ), selectivity, calibration curve and linearity, carry over, recovery and stability. The valid method was applied in pharmacokinetic study of one healthy subject after administration of 500mg extended release caplet of valproic acid. The blood was collected as much as 7mL for twelve spots, which are predose, 1, 2, 3, 4, 5, 8, 10, 24, 36, 48, and 72 hours after drug administration. Results: The calibration curve valproic acid was linear over the concentration range of 2.0 – 200.0 µg/mL (r = 0.9992). Within-run and between-run precision and accuracy were studied at four concentrations and RSDs were less than 1.8 % and 5.4 %, while the bias (accuracy values) were less than 17.9 % and 13.1 %, respectively. Conclusion: The developed method provides sensitivity, linearity, precision, accuracy and is suitable for analysis of valproic acid in plasma samples for pharmacokinetic studies.Keywords: Valproic acid, Nonanoic acid, HPLC, Validation, Liquid-liquid extraction.